Electrolyte for lithium-sulfur battery and lithium-sulfur battery comprising same

By using electrolytes containing ether-based solvents of cyclic ether and non-cyclic ether in lithium-sulfur batteries, the dissolution of polysulfides is suppressed, and the performance problems of lithium-sulfur batteries are solved during low-temperature operation, extending battery life and improving stability.

CN119487666APending Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380053346.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the lithium-sulfur battery is running at low temperature, the resistance of the electrolyte material increases due to the dissolution of the polysulfide from the positive electrode, which affects the low-temperature performance of the battery.

Method used

An electrolyte containing a non-aqueous solvent, a lithium salt, a nitrate/ester and a triaxane is used, wherein the ether-based solvent combination includes a cyclic ether and a non-cyclic ether to inhibit the dissolution of the polysulfide from the positive electrode.

Benefits of technology

By inhibiting the dissolution of polysulfides, the life of the lithium-sulfur battery is extended and the stability of the battery in the repeated charge and discharge cycle is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487666A_ABST
    Figure CN119487666A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrolyte for a lithium-sulfur battery and a lithium-sulfur battery comprising the same. The electrolyte for a lithium-sulfur battery contains a non-aqueous solvent, a lithium salt, a nitrate / ester, and a 3 # imgabs0 # alkane. The non-aqueous solvent contains an ether-based solvent. The ether-based solvent contains a cyclic ether and a non-cyclic ether.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrolyte for a lithium-sulfur battery and a lithium-sulfur battery including the electrolyte.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0186449 filed in Korea on December 27, 2022, the disclosure of which is incorporated herein by reference. Background Art

[0003] Lithium-sulfur batteries are battery systems that use a sulfur-sulfur (SS) bonded sulfur-based material as a positive electrode active material and lithium metal as a negative electrode active material. Sulfur, the main component of the positive electrode active material, exists in large quantities in nature and can be found all over the world, is non-toxic and has a low atomic weight.

[0004] As secondary batteries are used in a wide range of applications including electric vehicles (EVs) and energy storage systems (ESSs), lithium-sulfur battery technology has attracted attention, which achieves a theoretically higher energy storage density by weight (~2600 Wh / kg) than lithium-ion secondary batteries having a lower energy storage density by weight (~250 Wh / kg).

[0005] During discharge, the lithium-sulfur battery is oxidized by releasing electrons at the negative electrode active material lithium to become lithium cations, and is reduced by accepting electrons at the positive electrode active material (sulfur-based material). Through the reduction reaction, the sulfur-based material accepts two electrons through the SS bond and is converted into sulfur anions. The lithium cations generated by the oxidation reaction of lithium migrate to the positive electrode via the electrolyte and combine with the sulfur anions generated by the reduction reaction of the sulfur-based compound to form a salt. Specifically, the sulfur before discharge has a cyclic S8 structure, which is converted into lithium polysulfide (LiS) through the reduction reaction. x ) and is completely reduced to lithium sulfide (Li2S).

[0006] In this case, since the conductivity of sulfur in the sulfur-based compound as a positive electrode active material is low, it is difficult to ensure reactivity with electrons and lithium ions in the solid state. Therefore, in order to improve the reactivity of sulfur in lithium-sulfur batteries, a method for generating an intermediate polysulfide Li2S has been developed. x A technique to induce liquid phase reaction and improve reactivity. The technique uses an ether solvent such as dioxolane, dimethoxyethane (DME), etc., in which lithium polysulfide is highly soluble, as a solvent for the electrolyte. Therefore, the amount of electrolyte affects the reactivity of sulfur and battery life.

[0007] Recently, efforts have been devoted to the research and development of lithium-sulfur secondary batteries capable of low-temperature operation for aircraft and next-generation electric vehicles. However, low-temperature operation of lithium-sulfur secondary batteries remains challenging due to the dissolution of polysulfide (PS) from the cathode and the corresponding increase in electrolyte material resistance.

[0008] In summary, Li-S batteries operate through solid->liquid reactions, in which active materials are dissolved from the cathode in the form of PS during the first discharge (~2.3 V) and liquid->solid reactions, in which the dissolved PS moves back to the cathode during the second discharge (~2.1 V). In this case, the reaction efficiency of the dissolved PS moving back to the cathode is a factor that determines the degradation of lithium-sulfur secondary batteries.

[0009] Therefore, in order to improve the life of lithium-sulfur batteries, a technology for improving the conversion efficiency of polysulfide (PS) or controlling the amount of PS eluted from the cathode into the electrolyte is required. Summary of the invention

[0010] Technical issues

[0011] The present disclosure relates to providing an electrolyte for a lithium-sulfur battery having improved life characteristics by controlling the dissolution of polysulfide (PS) from a positive electrode and a lithium-sulfur battery using the same.

[0012] In particular, the present disclosure aims to provide a lithium-sulfur battery capable of long-term operation by preventing performance degradation of an electrolyte and degradation of a negative electrode by suppressing dissolution of polysulfide from a positive electrode.

[0013] Technical Solution

[0014] In order to solve the above-mentioned problems, according to one aspect of the present disclosure, an electrolyte for a lithium-sulfur battery according to the following embodiments is provided.

[0015] The lithium-sulfur battery electrolyte according to the first embodiment includes a non-aqueous solvent, a lithium salt, a nitrate / ester, and a trisulfur Alkane, wherein the non-aqueous solvent comprises an ether-based solvent, and wherein the ether-based solvent comprises a cyclic ether and a non-cyclic ether.

[0016] According to a second embodiment, in the first embodiment, the content of the cyclic ether may be 30% by volume or less based on the total volume of the nonaqueous solvent.

[0017] According to a third embodiment, in the first or second embodiment, the content of the cyclic ether may be 20% by volume or less based on the total volume of the nonaqueous solvent.

[0018] According to a fourth embodiment, in any one of the first to third embodiments, the content of the cyclic ether may be 20 volume % or less based on the total volume of the non-aqueous solvent, and the content of the acyclic ether may be 80 volume % or more based on the total volume of the non-aqueous solvent.

[0019] According to a fifth embodiment, in any one of the first to fourth embodiments, the nonaqueous solvent may not contain a carbonate-based solvent.

[0020] According to a sixth embodiment, in any one of the first to fifth embodiments, the cyclic ether may include 2-methylfuran, 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dihydropyran, 1,4-dihydropyran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetra ... alkane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, dimethyl isosorbide or a mixture thereof.

[0021] According to a seventh embodiment, in any one of the first to sixth embodiments, the acyclic ether may comprise dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether, ethylene glycol ethyl methyl ether, or a mixture thereof.

[0022] According to an eighth embodiment, in any one of the first to seventh embodiments, based on the total weight of the electrolyte for a lithium-sulfur battery, the three The content of alkane may be 5 wt % to 45 wt %.

[0023] According to a ninth embodiment, in any one of the first to eighth embodiments, based on the total weight of the electrolyte for a lithium-sulfur battery, the three The content of the alkane may be 10 wt % to 20 wt %.

[0024] According to a tenth embodiment, in any one of the first to ninth embodiments, the three The weight ratio of alkane to the nitrate may be from 2 to 15.

[0025] According to another aspect of the present disclosure, a lithium-sulfur battery of the following embodiment is provided.

[0026] A lithium-sulfur battery according to an eleventh embodiment includes a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, wherein the electrolyte is defined according to any one of the first to tenth embodiments, and wherein the positive electrode includes a sulfur-containing compound as a positive electrode active material.

[0027] According to a twelfth embodiment, in the eleventh embodiment, the sulfur-containing compound may include inorganic sulfur (S8), Li2S n (n≥1), disulfide compounds, organic sulfur compounds, carbon-sulfur polymers (C2S x ) n , x is an integer from 2.5 to 50, n≥2) or a mixture thereof.

[0028] According to a thirteenth embodiment, in the eleventh or twelfth embodiment, the negative electrode may include lithium metal, lithium alloy, or a mixture thereof as a negative electrode active material.

[0029] According to a fourteenth embodiment, in any one of the eleventh to thirteenth embodiments, the lithium-sulfur battery may be a coin type battery or a pouch type battery.

[0030] Beneficial Effects

[0031] The electrolyte for a lithium-sulfur battery according to one embodiment of the present disclosure can suppress the dissolution of polysulfide (PS) from a positive electrode.

[0032] Therefore, the electrolyte for a lithium-sulfur battery according to one embodiment of the present disclosure can prevent the degradation of the positive electrode, the electrolyte, and the negative electrode during repeated charge and discharge cycles of the lithium-sulfur battery, thereby improving the life characteristics of the battery.

[0033] The electrolyte for a lithium-sulfur battery according to one embodiment of the present disclosure may have a beneficial effect on a lithium-sulfur battery having high energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings illustrate exemplary embodiments of the present disclosure and, together with the foregoing description, serve to provide a further understanding of the technical aspects of the present disclosure, and thus the present disclosure should not be construed as being limited to the accompanying drawings.

[0035] Figure 1It is a figure showing the evaluation results of Experimental Example 1 in the present disclosure.

[0036] Figure 2 It is a figure showing the evaluation results of Experimental Example 1 in the present disclosure.

[0037] Figure 3 It is a figure showing the evaluation results of Experimental Example 2 in the present disclosure.

[0038] Figure 4 It is a figure showing the evaluation results of Experimental Example 2 in the present disclosure.

[0039] Figure 5 It is a figure showing the evaluation results of Experimental Example 3 in the present disclosure.

[0040] Figure 6 It is a figure showing the evaluation results of Experimental Example 3 in the present disclosure.

[0041] Figure 7 It is a figure showing the evaluation results of Experimental Example 4 in the present disclosure.

[0042] Figure 8 It is a figure showing the evaluation results of Experimental Example 4 in the present disclosure.

[0043] Fig. 9 It is a figure showing the evaluation results of Experimental Example 4 in the present disclosure. Detailed Description

[0044] Hereinafter, the present disclosure will be described in detail. However, the present disclosure is not limited to the following description, and various modifications or selective combinations of the elements can be made if necessary. Therefore, it should be understood that the present disclosure encompasses all modifications, equivalents, or alternatives included in the aspects and technical scope of the present disclosure.

[0045] The term "comprising" used in this specification specifies the presence of the stated elements, but does not exclude the presence or addition of one or more other elements, unless the context clearly indicates otherwise.

[0046] As used herein, the term "polysulfide (PS)" encompasses the concepts of "polysulfide ion (S x 2- , 1 < x ≤ 8)" and "lithium (poly) sulfide (Li2S x or LiS x - , 1 < x ≤ 8)".

[0047] During the operation of a lithium-sulfur battery, polysulfides (PS, LiS x) is dissolved from the cathode into the electrolyte, in which case, when the electrolyte has a high solvent to polysulfide ratio, overvoltage occurs due to the high concentration of polysulfides in the solvent. As described above, due to the shuttling effect of lithium polysulfides dissolved from the cathode into the electrolyte during charge and discharge, the lithium-sulfur battery suffers from rapid capacity decay in repeated charge and discharge cycles.

[0048] Therefore, the electrolyte for a lithium-sulfur battery according to one aspect of the present disclosure uses a solvent combination and an additive having a non-solvent characteristic for polysulfides to suppress the dissolution of polysulfides into the electrolyte and solve the above-mentioned problems.

[0049] Electrolytes for lithium secondary batteries

[0050] The lithium-sulfur battery electrolyte according to one aspect of the present disclosure comprises a non-aqueous solvent, a lithium salt, a nitrate / ester and a trisulfide alkyl,

[0051] wherein the non-aqueous solvent comprises an ether solvent, and

[0052] The ether solvent comprises cyclic ether and non-cyclic ether.

[0053] In this disclosure, the three Alkanes are a general term for organic compounds having a molecular formula of C3H6O3 and consisting of a six-membered ring having three carbon atoms and three oxygen atoms. Alkanes can have three isomers, and the three The alkanes may specifically include 1,2,3-tri Alkane, 1,2,4-tri Alkane, 1,3,5-tri Alkane or a mixture thereof.

[0054] In one embodiment of the present disclosure, the three The alkane may contain 1,3,5-tri alkyl.

[0055] According to one embodiment of the present disclosure, when the three When an alkane is added to the lithium-sulfur battery electrolyte, the solubility of polysulfide in the nonaqueous solvent, particularly the ether solvent, can be reduced, thereby suppressing the dissolution of polysulfide from the positive electrode, but the mechanism of the present disclosure is not limited thereto.

[0056] According to one aspect of the present disclosure, the nonaqueous solvent is a medium in which ions participating in the electrochemical reaction of the lithium secondary battery can move, and is used to dissolve the lithium salt, the nitrate / ester and / or the trioxide. alkyl.

[0057] According to one aspect of the present disclosure, the electrolyte for a lithium-sulfur battery includes the ether-based solvent as the nonaqueous solvent, and in particular, the ether-based solvent includes two types of ether-based solvents such as cyclic ether and non-cyclic ether.

[0058] In one embodiment of the present disclosure, the non-aqueous solvent may contain 80% by volume or more, for example, 85% by volume to 100% by volume, 90% by volume to 100% by volume, 95% by volume to 100% by volume, 98% by volume to 100% by volume, 90% by volume to 98% by volume, or 90% by volume to 95% by volume of the ether solvent, based on the total volume of the non-aqueous solvent. When the amount of the ether solvent is within the above range based on the total volume of the non-aqueous solvent, it may have an effect on the lithium salt, the nitrate / ester and the trioxide. The solubility of the alkane has a beneficial effect, but the disclosure is not limited in this regard.

[0059] In one embodiment of the present disclosure, for example, the cyclic ether can be used as a non-solvent for polysulfide dissolved from the positive electrode to inhibit the dissolution of polysulfide. In one embodiment of the present disclosure, based on the total volume of the non-aqueous solvent, the content of the cyclic ether can be, for example, 30% by volume or less, 25% by volume or less, 20% by volume or less, 15% by volume or less, specifically 1% by volume to 20% by volume, or 5% by volume to 20%. When the amount of the cyclic ether is within the above range, it can inhibit the dissolution of polysulfide and the lithium salt, the nitrate / ester and the trisulfide. The solubility of the alkane has a beneficial effect, but the disclosure is not limited in this regard.

[0060] In another embodiment of the present disclosure, the non-aqueous solvent may contain the cyclic ether in an amount of 20 vol% or less, and the acyclic ether in an amount of 80 vol% or more, e.g., 85 vol% or more, 80 vol% to 99 vol%, or 80 vol% to 90 vol%, based on the total volume.

[0061] In one embodiment of the present disclosure, the cyclic ether may include, for example, 2-methylfuran, 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dihydropyran, 1,4-dihydropyran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetra ... Preferably, the cyclic ether may include at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran and 2,5-dimethyltetrahydrofuran. More preferably, the cyclic ether may include 2-methylfuran.

[0062] In one embodiment of the present disclosure, the cyclic ether may preferably contain a conjugated heterocyclic compound. For example, the conjugated heterocyclic compound contains a heterocyclic compound containing at least two double bonds and containing either an oxygen atom or a sulfur atom, and forms a polymer passivation layer (solid electrolyte interface (SEI) layer) on the surface of the lithium metal (negative electrode) through the ring-opening reaction of the heterocyclic compound in the initial discharge stage of the battery, thereby inhibiting the growth of lithium dendrites, and further reducing the electrolyte decomposition on the surface of the lithium metal and its corresponding side reactions, resulting in a longer life of the lithium-sulfur battery. In addition, due to the delocalization of the lone pair of electrons of the heteroatom (oxygen atom or sulfur atom), the conjugated heterocyclic compound cannot easily dissolve salts, thereby reducing the amount of polysulfide dissolved into the electrolyte. The conjugated heterocyclic compound can be a substituted or unsubstituted heterocyclic compound selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group (-NO2), an amine group (-NH2) or a sulfonyl group (-SO2). In addition, the conjugated heterocyclic compound can be a polycyclic compound of a heterocyclic compound and at least one of a cyclic alkyl group having 3 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms.

[0063] In one embodiment of the present disclosure, the conjugated heterocyclic compound may include, for example, at least one selected from the group consisting of furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran and 2-(2-nitrovinyl)furan, but is not limited thereto, and 2-methylfuran may be the most preferred.

[0064] Therefore, in one embodiment of the present disclosure, the cyclic ether may consist of 2-methylfuran (2-MeF), but the present disclosure is not limited thereto.

[0065] In one embodiment of the present disclosure, the non-cyclic ether may include, for example, dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether, ethylene glycol ethyl methyl ether or a mixture thereof. Preferably, the non-cyclic ether may include at least one selected from the group consisting of dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether. More preferably, the acyclic ether may comprise dimethoxyethane.

[0066] In one embodiment of the present disclosure, the non-cyclic ether may consist of dimethoxyethane (DME).

[0067] In one embodiment of the present disclosure, the non-aqueous solvent may include 2-methylfuran and dimethoxyethane.

[0068] In addition, the non-aqueous solvent may contain the cyclic ether and the acyclic ether in a volume ratio of 5:95 to 95:5, preferably 5:95 to 50:50, 10:90 to 30:70, most preferably 15:85 to 25:75, or 20:80. The volume ratio is the ratio of "volume % of the cyclic ether" to "volume % of the acyclic ether" in the non-aqueous solvent.

[0069] In one embodiment of the present disclosure, in addition to the ether solvent, the non-aqueous solvent may further include a solvent capable of dissolving the lithium salt, the nitrate / ester and the tri- Any organic solvent of alkanes, for example, any organic solvent used in lithium secondary battery electrolytes, such as esters, amides, linear carbonates and cyclic carbonates, and in one embodiment of the present disclosure, on the basis of including the ether solvent, the non-aqueous solvent may also include any non-aqueous solvent used in lithium secondary battery electrolytes. However, preferably, the lithium salt, the nitrate / ester and the tris(III) In terms of solubility of alkanes, the electrolyte for lithium secondary batteries may not contain a carbonate-based solvent as the nonaqueous solvent.

[0070] In one embodiment of the present disclosure, the ester may include, for example, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone, or a mixture thereof, but is not limited thereto.

[0071] In one embodiment of the present disclosure, the carbonate not included in the electrolyte for a lithium-sulfur battery may include a linear carbonate, a cyclic carbonate, or a mixture thereof.

[0072] The linear carbonate may generally include, for example, any one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate, or a mixture thereof, but is not limited thereto.

[0073] The cyclic carbonate may generally include, for example, any one or a mixture thereof selected from the group consisting of ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, but is not limited thereto. In addition, the halide may include, for example, fluoroethylene carbonate, but is not limited thereto.

[0074] In another embodiment of the present disclosure, because the carbonate-based solvent does not dissolve the nitrate / ester and / or the trioxide Alkanes or have low solubility, so the non-aqueous solvent may not contain the carbonate-based solvent.

[0075] In another embodiment of the present disclosure, the non-aqueous solvent may be such that the carbonate solvent does not affect the nitrate / ester and / or the triterpenoid. A small amount of the carbonate-based solvent is included to improve the solubility of the non-aqueous solvent in the alkane. For example, when the non-aqueous solvent includes the carbonate-based solvent, the amount of the carbonate-based solvent can be 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or 0 wt % (i.e., zero) based on the total weight of the lithium secondary battery electrolyte.

[0076] In one embodiment of the present disclosure, the lithium-sulfur battery electrolyte may include, for example, 5 wt % to 45 wt %, specifically 10 wt % to 40 wt %, 10 wt % to 30 wt %, 10 wt % to 25 wt %, or 10 wt % to 20 wt % of the three compounds based on the total weight of the lithium-sulfur battery electrolyte. When the three When the amount of alkane is within the above range, the addition of the trialkylene The alkane may have beneficial effects on polysulfide dissolution suppression and improvement of life characteristics of a lithium-sulfur battery using the same, but the present disclosure is not limited thereto.

[0077] In one embodiment of the present disclosure, the lithium salt is contained in the electrolyte for the lithium-sulfur battery as an electrolyte salt, and may include any lithium salt commonly used in the electrolyte of the lithium-sulfur battery without limitation. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborate, lower aliphatic lithium carbonate, lithium tetraphenylborate, lithium imide or a mixture thereof, but not limited thereto.

[0078] In one embodiment of the present disclosure, the lithium salt may not include lithium nitrate. Lithium nitrate may be included as an example of the above-mentioned nitrate / ester.

[0079] In one embodiment of the present disclosure, the lithium salt may include lithium bis(fluorosulfonyl)imide (LiFSI).

[0080] In one embodiment of the present disclosure, the lithium salt may consist of lithium bis(fluorosulfonyl)imide (LiFSI).

[0081] In one embodiment of the present disclosure, the concentration of the lithium salt may be appropriately determined in consideration of ion conductivity and solubility, and may be, for example, 0.1 to 4.0 M, 0.5 to 2.0 M, 0.5 to 1.0 M, or 0.5 M. When the lithium salt concentration is within the above range, it may have a beneficial effect on ion conductivity and electrolyte viscosity, but is not limited thereto.

[0082] In one embodiment of the present disclosure, based on the lithium salt, when the nitrate / ester is dissolved in the electrolyte of the lithium secondary battery, the nitrate / ester can be used to provide ions, thereby improving the conductivity of the lithium secondary battery, and when the electrolyte for lithium secondary batteries is used in the lithium-sulfur battery, the battery life characteristics are improved. Specifically, the efficacy of the nitrate / ester is not limited thereto, but for example, the nitrate / ester can inhibit the reduction reaction of lithium polysulfide during the charge and discharge of the lithium-sulfur battery and prevent the irreversible consumption of lithium polysulfide, thereby improving the performance of the lithium-sulfur battery.

[0083] In one embodiment of the present disclosure, the nitrate / ester may include, but is not limited to, any type of nitrate / ester that forms a stable coating on the negative electrode, i.e., the lithium metal electrode, of the lithium secondary battery, specifically the lithium-sulfur battery, and improves the charge and discharge efficiency, and may include, for example, nitric acid compounds, nitrite compounds, or mixtures thereof.

[0084] In one embodiment of the present disclosure, the nitrate / ester can be, for example, selected from the group consisting of: inorganic nitric acid or nitrous acid compounds, such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), ammonium nitrite (NH4NO2); organic nitric acid or nitrous acid compounds, such as methyl nitrate, dialkyl imidazole nitrate , guanidine nitrate, imidazole nitrate , pyridine nitrate , ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite; organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, but not limited thereto.

[0085] In one embodiment of the present disclosure, the cation of the nitrate may be selected from alkali metals such as lithium, sodium, potassium, rubidium, and cesium, but is not limited thereto.

[0086] In another embodiment of the present disclosure, the nitrate may comprise lithium nitrate (LiNO 3 ).

[0087] In one embodiment of the present disclosure, based on the total weight of the lithium secondary battery electrolyte, the content of the nitrate may be, for example, 1 wt % to 10 wt %, 2 wt % to 10 wt %, or 3 wt % to 10 wt %, specifically 3 wt % to 8 wt %, 3 wt % to 6 wt %, or 3 wt % to 5 wt %, but is not limited thereto. When the nitrate is included in the above amount, the nitrate may have a beneficial effect on the conductivity of the electrolyte and, when used in the lithium-sulfur battery, has a beneficial effect on polysulfide dissolution inhibition, but the present disclosure is not limited thereto.

[0088] In one embodiment of the present disclosure, the content of the nitrate / ester may be such that the three The weight ratio of the alkane to the nitrate is 2 to 15, specifically 3 to 10, 3 to 8, or 3.3 to 7, but the present disclosure is not limited thereto.

[0089] In another embodiment of the present disclosure, on the basis of the above composition, the lithium-sulfur battery electrolyte may further include additives to improve the charge and discharge characteristics and flame retardancy. The present disclosure is not limited to a specific type of additive, but the additive may include, for example, pyridine, triethyl phosphite, triethanolamine, ethylenediamine, n-glyme, hexamethylphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted The compounds include oxazolidinone, N,N-substituted imidazolidine, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, fluoroethylene carbonate (FEC), propene sultone (PRS) and vinylene carbonate (VC).

[0090] The electrolyte for a lithium-sulfur battery according to one aspect of the present disclosure may be prepared by a method commonly used in the art, and the present disclosure is not limited to a specific method.

[0091] Lithium-sulfur battery

[0092] A lithium-sulfur battery according to another aspect of the present disclosure comprises the above-mentioned lithium-sulfur battery electrolyte, a positive electrode comprising a positive electrode active material, and a negative electrode comprising a negative electrode active material. Specifically, the lithium-sulfur battery comprises the positive electrode, the negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.

[0093] [positive electrode]

[0094] The positive electrode may include a positive electrode current collector and a positive electrode active material layer on one or both surfaces of the positive electrode current collector.

[0095] The positive electrode current collector is not limited to a specific type, and may include any positive electrode current collector that supports the positive electrode active material and has high conductivity without causing any chemical changes in the battery. For example, the positive electrode current collector may include copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, copper or stainless steel whose surface is treated with carbon, nickel or silver, aluminum-cadmium alloy, etc.

[0096] The positive electrode current collector may have fine concavoconvexities on the surface to increase the bonding strength with the positive electrode active material, and may have various forms, for example, a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a non-woven fabric, and the like.

[0097] The positive electrode active material layer includes the positive electrode active material, and may further include a conductive material, a binder, and an additive.

[0098] The positive electrode active material may include a sulfur-carbon composite, which includes a porous carbon material and sulfur in at least a portion of the interior of the porous carbon material and the outer surface of the porous carbon material. Since the sulfur contained in the positive electrode active material itself does not have conductivity, sulfur is used in combination with a conductive material such as a carbon material. Therefore, the sulfur is contained in the form of a sulfur-carbon composite.

[0099] In one embodiment of the present disclosure, the positive electrode active material may include elemental sulfur, a sulfur compound or a mixture thereof. Specifically, the positive electrode active material may include inorganic sulfur (S8), Li2S n (n≥1), disulfide compounds, organic sulfur compounds, carbon-sulfur polymers (C2S x )n, x=2.5 to 50, n≥2) or a mixture thereof. Preferably, the sulfur may be inorganic sulfur.

[0100] The sulfur-carbon composite includes the porous carbon material to provide a framework for uniformly and stably fixing sulfur and to compensate for low electrical conductivity of the sulfur, thereby enhancing an electrochemical reaction.

[0101] The porous carbon material can generally be prepared by carbonizing various carbon precursors. The porous carbon material contains irregular pores. The average diameter of the pores can be in the range of 1 to 200 nm, and the porosity can be in the range of 10 to 90 volume % of the total volume of the porous carbon material. When the average diameter of the pores is less than the above range, the pore size is only at the molecular level, making it impossible to load sulfur. On the contrary, when the average diameter of the pores exceeds the above range, it is not suitable for electrode manufacturing processes due to the low mechanical strength of the porous carbon material.

[0102] In one embodiment of the present disclosure, the "average diameter of the pores" can be measured by known methods for measuring the pore size of porous materials, and the measuring method is not particularly limited. For example, the pore size can be measured by electron scanning microscopy (SEM), field emission electron microscopy or laser diffraction. Measurement using laser diffraction can be performed, for example, using a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT 3000).

[0103] In one embodiment of the present disclosure, "porosity" refers to the ratio of the volume occupied by pores to the total volume of the structure, in units of volume %, and can be used interchangeably with the terms porosity, void fraction, etc. In the present disclosure, the method for measuring the porosity is not particularly limited. According to one embodiment of the present disclosure, the porosity can be measured by the BET method using nitrogen, mercury (Hg) porosimetry, or ASTM D2873.

[0104] The porous carbon material may be in the shape of a sphere, a rod, a needle, a plate, a tube, or a block, and is not limited to a specific shape, and may be any shape commonly used in the lithium-sulfur battery.

[0105] The porous carbon material may include any porous carbon material commonly used in the art having a porous structure and a large specific surface area. For example, the porous carbon material may include at least one selected from the group consisting of: graphite; graphene; carbon black, such as Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNTs), such as single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), etc.; carbon fibers, such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), etc.; graphites, such as natural graphite, artificial graphite, expandable graphite, etc.; and activated carbon, but not limited thereto. Preferably, the porous carbon material may be a carbon nanotube.

[0106] In the sulfur-carbon composite according to the present disclosure, the sulfur may be arranged in at least one of the interior of the porous carbon material or the outer surface of the porous carbon material, and may be present in an area of ​​less than 100%, preferably 1% to 95%, and more preferably 40% to 96% of the interior of the porous carbon material and the outer surface of the porous carbon material, for example. When the sulfur is present in the interior of the porous carbon material and the outer surface of the porous carbon material within the above range, the maximum effect can be exhibited in terms of electron transport area and electrolyte wetting. Specifically, when the sulfur is thinly and uniformly loaded into the above-mentioned area range inside the porous carbon material and on the outer surface of the porous carbon material, the electron transport contact area during charge and discharge can be increased. When the sulfur is located in an area corresponding to 100% of the interior of the porous carbon material and the outer surface of the porous carbon material, the porous carbon material is completely covered by the sulfur, resulting in poor electrolyte wetting, little or no contact, and thus unable to accept electrons and participate in electrochemical reactions.

[0107] The sulfur-carbon composite may, for example, contain sulfur in an amount of 65 wt % or more, specifically 65 to 90 wt %, 70 to 85 wt %, or 72 to 80 wt %, based on 100 wt % of the sulfur-carbon composite. When the sulfur content is within the above range, it may have a beneficial effect on the performance and capacity of the battery, but the present disclosure is not limited thereto.

[0108] The sulfur-carbon composite of the present disclosure can be manufactured by any method commonly used in the art without limitation. For example, the composite can be prepared by simply mixing the sulfur with the porous carbon material and then heat-treating the mixture.

[0109] In one embodiment of the present disclosure, based on the above composition, the positive electrode active material may further include at least one additive selected from transition metal elements, Group IIIA elements, Group IVA elements, compounds of these elements with sulfur, and alloys of these elements with sulfur.

[0110] The transition metal element may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au or Hg, the IIIA group element may include Al, Ga, In, Ti, etc., and the IVA group element may include Ge, Sn, Pb, etc.

[0111] Based on the total weight of the positive electrode active material layer, the positive electrode for the lithium secondary battery of the present disclosure may include, for example, 80% by weight or more, specifically 80% by weight to 100% by weight, more specifically 85% by weight to 98% by weight, or 80% by weight to 95% by weight of the positive electrode active material. Based on the total 100% by weight of the positive electrode active material layer, the lower limit of the amount of the positive electrode active material may be 70% by weight or more or 85% by weight or more, and based on the total 100% by weight of the positive electrode active material layer, the upper limit may be 99% by weight or less or 90% by weight or less. The amount of the positive electrode active material can be set by a combination of a lower limit and an upper limit. When the amount of the positive electrode active material is less than the above range, the relative amount of auxiliary materials such as conductive materials and adhesives is high, while the amount of the positive electrode active material is low, which makes it difficult to achieve a battery with high capacity and high energy density. On the contrary, when the amount of the sulfur-carbon composite exceeds the above range, the relative amount of the conductive material or adhesive as described below is low, and the physical properties of the electrode are reduced.

[0112] The conductive material serves as a movement path of electrons from the current collector to the positive active material by electrically connecting an electrolyte to the positive active material, and may include any material having conductive properties as an electrode component physically different from carbon contained in the sulfur-carbon composite without limitation.

[0113] For example, the conductive material may include: carbon black, such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black, etc.; carbon derivatives, such as carbon nanotubes, fullerenes, etc.; conductive fibers, such as carbon fibers, metal fibers, etc.; fluorocarbons; metal powders, such as aluminum powder, nickel powder, etc.; or conductive polymers, such as polyaniline, polythiophene, polyacetylene, polypyrrole, etc. (used alone or in combination).

[0114] Based on the total weight of the positive electrode active material, the amount of the conductive material may be 1 to 10 wt %. When the amount of the conductive material is less than the above range, the electron transfer between the positive electrode active material and the current collector is reduced, resulting in lower voltage and capacity. On the contrary, when the amount of the conductive material exceeds the above range, the relative proportion of the positive electrode active material is low, and the total energy (charge) of the battery may be reduced. Therefore, it is preferred to determine the optimal amount within the above range.

[0115] The binder bonds the positive electrode active material to the positive electrode current collector and interconnects the positive electrode active materials to increase bonding strength, and may include any binder known in the art.

[0116] For example, the adhesive may include any one selected from the group consisting of: a fluororesin-based adhesive, including polyvinylidene fluoride (PVdF), a polyvinylidene fluoride-based polymer containing at least one vinylidene fluoride as a repeating unit, polytetrafluoroethylene (PTFE) or a mixture thereof; a rubber-based adhesive, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber and styrene-isoprene rubber; an acrylic-based adhesive; a cellulose-based adhesive, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; a polyol-based adhesive; a polyolefin-based adhesive, including polyethylene and polypropylene; a polyimide-based adhesive; a polyester-based adhesive; and a silane-based adhesive; and a mixture thereof or a copolymer thereof.

[0117] Based on the total weight of the positive electrode active material layer, the amount of the binder may be 1 to 10 wt %. When the amount of the binder is less than the above range, the physical properties of the positive electrode may be reduced, and the positive electrode active material and the conductive material may be desorbed. When the amount of the binder exceeds the above range, the relative proportion of the positive electrode active material and the conductive material in the positive electrode is low, resulting in low battery capacity. Therefore, it is preferred to determine the optimal amount within the above range.

[0118] In the present disclosure, a method of manufacturing the positive electrode for a lithium secondary battery is not particularly limited, and may include any method known to those skilled in the art or a variation thereof.

[0119] For example, the positive electrode for a lithium secondary battery may be manufactured by preparing a positive electrode slurry composition having the above composition, and coating the positive electrode slurry composition on at least one surface of the positive electrode collector to form the positive electrode active material layer.

[0120] The positive electrode slurry composition includes the positive electrode active material described above, and may further include the binder, the conductive material, and a solvent.

[0121] The solvent includes any solvent that promotes uniform dispersion of the positive electrode active material. The solvent may include an aqueous solvent, most preferably water, and in this case, the water may be distilled water or deionized water. However, the present disclosure is not necessarily limited thereto, and if desired, a lower alcohol that is easily mixed with water may be used. The lower alcohol may include methanol, ethanol, propanol, isopropanol and butanol, and preferably, a mixture of a lower alcohol and water may be used.

[0122] The solvent may be included at a sufficient concentration level to facilitate coating, and the specific amount may vary depending on the coating method and apparatus.

[0123] If necessary, the positive electrode slurry composition may further include materials commonly used in the corresponding technical field to improve functions. For example, the materials may include a viscosity modifier, a flow aid, a filler, and the like.

[0124] The method of coating the positive electrode slurry composition is not particularly limited in the present disclosure, and may include, for example, doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be coated on the positive electrode collector by pressing or laminating after forming on a substrate.

[0125] After the coating, a drying process may be performed to remove the solvent. The drying process may be performed at a suitable temperature and time to remove the solvent, and the conditions may vary depending on the type of solvent and are not particularly limited in the present disclosure. For example, the drying method may include drying with warm air, hot air or low humidity air, vacuum drying, and drying by (far) infrared radiation or electron beam radiation, etc. The drying speed is usually adjusted to remove the solvent as quickly as possible within a speed range where cracking does not occur in the positive active material layer due to stress concentration or the positive active material layer is peeled off from the positive current collector.

[0126] In addition, after the drying, the current collector may be pressed to increase the density of the positive electrode active material in the positive electrode. The pressing method may include molding, rolling, and the like.

[0127] The positive electrode, specifically the positive electrode active material layer manufactured by the above-mentioned composition and manufacturing method, can have a porosity of 50 to 80 volume %, specifically 60 to 75 volume %. When the porosity of the positive electrode is less than 50 volume %, the filling level of the positive electrode slurry composition comprising the positive electrode active material, the conductive material and the binder is too high, so that it is impossible to maintain enough electrolyte for showing ionic conductivity and / or conductivity in the positive electrode active material. As a result, the output characteristics or cycle characteristics of the battery may deteriorate, which causes severe overvoltage and discharge capacity reduction of the battery. On the contrary, when the porosity of the positive electrode is too high and exceeds 80 volume %, it may cause poor physical and electrical connection with the collector, low adhesion strength and no or small reaction, and electrolyte filling at high porosity may reduce the energy density of the battery. Therefore, the porosity is appropriately adjusted within the above range.

[0128] [negative electrode]

[0129] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on one or both surfaces of the negative electrode current collector. Alternatively, the negative electrode may be a lithium metal plate.

[0130] The negative electrode current collector is configured to support the negative electrode active material layer as described in the positive electrode current collector.

[0131] The negative electrode active material layer may include a negative electrode active material, and may further include a conductive material, a binder, etc. In this case, the conductive material and the binder follow the above description.

[0132] The negative electrode active material may include a material capable of reversibly inserting or deinserting lithium (Li + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.

[0133] The reversible insertion and extraction of lithium ions (Li + ) may include, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may include, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may include, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0134] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of lithium metal foil or lithium metal powder.

[0135] In one embodiment of the present disclosure, the negative electrode may be a lithium metal foil or a lithium alloy foil.

[0136] In one embodiment of the present disclosure, the negative electrode may have a small thickness to improve the energy density of the lithium-sulfur battery, for example, the thickness may be 20 μm to 120 μm, specifically 20 μm to 100 μm, 30 μm to 80 μm, 40 μm to 70 μm, or 50 μm to 60 μm. The thickness of the negative electrode may be measured using a thickness gauge of Mitutoyo, or may be determined by a SEM image of a cross section of the negative electrode, and the measuring method is not particularly limited.

[0137] [Diaphragm]

[0138] The separator separates or insulates the positive electrode from the negative electrode and enables lithium ions to be transferred between the positive electrode and the negative electrode. The separator may be made of a porous non-conductive or insulating material, not limited to a particular type, and may include any separator commonly used in lithium secondary batteries. The separator may be an independent component such as a membrane, and may also be a coating added to the positive electrode and / or the negative electrode.

[0139] The separator may preferably have low resistance to the movement of electrolyte ions and high electrolyte absorption capacity.

[0140] The separator may include a porous substrate, and the porous substrate may include any porous substrate commonly used in secondary batteries, and may be used alone or in a stacked form. For example, a nonwoven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, or a polyolefin-based porous membrane may be used, but is not limited thereto.

[0141] In the present disclosure, the porous substrate is not limited to a specific material, and may include any of the porous substrates generally used in electrochemical devices. For example, the porous substrate may include at least one type of material selected from the group consisting of polyolefins (such as polyethylene, polypropylene, etc.), polyesters (such as polyethylene terephthalate, polybutylene terephthalate, etc.), polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzodione), ... azoles) and polyarylates.

[0142] The thickness of the porous substrate may be 1 to 100 μm, preferably 5 to 50 μm, but is not limited thereto. Although the thickness of the porous substrate is not limited to the above range, when the thickness is too much less than the above lower limit, the mechanical properties may be reduced and the separator may be easily damaged when the battery is used.

[0143] The porous substrate may have an average pore diameter of 0.001 to 50 μm and a porosity of 10 to 95 volume %, but is not limited thereto.

[0144] The lithium-sulfur battery according to the present disclosure may adopt a commonly used winding process and a lamination or stacking and folding process of a separator and an electrode.

[0145] The lithium-sulfur battery is not limited to a specific shape and may have various shapes, for example, a cylindrical shape, a stacked type, a coin type, a pouch type, and the like.

[0146] Hereinafter, the present disclosure will be described in more detail through embodiments. However, the following embodiments are provided by way of example, and the scope of the present disclosure is not limited thereto.

[0147] [Manufacturing of lithium-sulfur batteries]

[0148] Example 1

[0149] Preparation of electrolyte for lithium-sulfur batteries

[0150] 0.5 M lithium bis(fluorosulfonyl)imide (LiFSI), 3 wt% lithium nitrate (LiNO3, molar mass 69 g / mol) and 10 wt% 1,3,5-triazine were mixed. To a mixture of 2-methylfuran (2MeF) and 1,2-dimethoxyethane (DME) (2:8 v / v), TOX (molar mass 90.08 g / mol) was added and stirred at room temperature (23° C.) for 12 hours to prepare an electrolyte.

[0151] Electrode preparation

[0152] A sulfur-carbon composite (S8:CNT=75:25 (weight ratio)) as a positive electrode active material and polyacrylic acid (PAA) as a binder were mixed in a weight ratio of 95:5 in distilled water as a solvent to prepare a positive electrode slurry.

[0153] The positive electrode slurry composition was coated on both surfaces of a 12 μm thick aluminum current collector, dried at 80° C., and rolled using a roller press to prepare a positive electrode. In this case, the loading amount of the positive electrode active material was 2.9 mAh / cm 2 .

[0154] For the negative electrode, a 50 μm thick lithium metal foil was prepared.

[0155] Lithium-sulfur battery manufacturing

[0156] The positive electrode and the negative electrode prepared as above were placed and stacked with a polyethylene separator having a thickness of 16 μm and a porosity of 68 volume % interposed therebetween to assemble a pouch type battery, and 1 g of the prepared electrolyte was injected into the pouch type battery, followed by sealing to manufacture a pouch type lithium-sulfur battery.

[0157] Example 2

[0158] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 20 wt % of 1,3,5-triazine was added. Alkane (TOX).

[0159] Example 3

[0160] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 30 wt % of 1,3,5-triazine was added. Alkane (TOX).

[0161] Example 4

[0162] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 40 wt % of 1,3,5-triazine was added. Alkane (TOX).

[0163] Example 5

[0164] Preparation of electrolyte for lithium-sulfur batteries

[0165] 0.5 M lithium bis(fluorosulfonyl)imide (LiFSI), 3 wt% lithium nitrate (LiNO3, molar mass 69 g / mol) and 10 wt% 1,3,5-triazine were mixed. To a mixture of 2-methylfuran (2MeF) and 1,2-dimethoxyethane (DME) (2:8 v / v), TOX (molar mass 90.08 g / mol) was added and stirred at room temperature (23° C.) for 12 hours to prepare an electrolyte.

[0166] Electrode preparation

[0167] A mixture of sulfur-carbon composite (S8:CNT=75:25 (weight ratio)) as a positive electrode active material and carboxymethyl cellulose (CMC):polyacrylic acid (PAA):styrene butyl rubber (SBR) (0.5:1.5:2.0 weight ratio) as a binder were mixed in distilled water as a solvent at a weight ratio of 96:4 to prepare a positive electrode slurry.

[0168] The positive electrode slurry composition was coated on both surfaces of a 12 μm thick aluminum current collector, dried at 80° C., and rolled using a roller press to prepare a positive electrode. In this case, the loading amount of the positive electrode active material was 3.0 mAh / cm 2 .

[0169] For the negative electrode, a 50 μm thick lithium metal foil was prepared.

[0170] Lithium-sulfur battery manufacturing

[0171] The positive electrode and the negative electrode prepared as above were placed and stacked together with a polyethylene separator having a thickness of 16 μm and a porosity of 68 volume % interposed therebetween to assemble a pouch-type battery, 1 g of the prepared electrolyte was injected into the pouch-type battery, and then sealed to manufacture a pouch-type lithium-sulfur battery.

[0172] Example 6

[0173] A lithium-sulfur battery was manufactured by the same method as in Example 5, except that, as the lithium salt, 0.5 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added instead of 0.5 M lithium bis(fluorosulfonyl)imide (LiFSI).

[0174] Example 7

[0175] A lithium-sulfur battery was manufactured by the same method as in Example 6, except that, as the nonaqueous solvent, 1,3-dioxolane (DOL) was used with DOL:DME (2:8 v / v) instead of 2-MeF.

[0176] Comparative Example 1

[0177] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 1,3,5-triazine was not added. Alkane (TOX).

[0178] Comparative Example 2

[0179] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that, for the non-aqueous solvent, 1,3-dioxolane and 1,2-dimethoxyethane (1:1 v / v) were used instead of 2-MeF:DME (2:8 v / v), and 1,3,5-trimethoxyethane was not added. Alkane (TOX).

[0180] Comparative Example 3

[0181] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that 1,3-dioxolane and monofluoroethylene carbonate were used as the nonaqueous solvent, and 1,3,5-trifluoroethylene carbonate was added. Alkane, making 1,3,5-tri The volume ratio of alkane:1,3-dioxolane:monofluoroethylene carbonate was 10:80:10, and 0.5 M of LiFSI and 3 wt % of LiNO 3 were added.

[0182] Experimental Example 1. Battery performance evaluation with and without TOX and its results

[0183] The performance of each battery of Example 1 and Comparative Example 1 was evaluated by the following method.

[0184] The battery performance was evaluated by 6 cycles of charge and discharge at 1.8 V to 2.5 V cutoff conditions at 25 °C for activation (each cycle was a 0.5 C charge / 0.5 C discharge cycle), followed by repeated 0.3 C charge / 1 C discharge CC mode cycles, Figure 1 and Figure 2 The results are shown.

[0185] refer to Figure 1 and Figure 2 It was confirmed that, when TOX was included in the lithium-sulfur battery electrolyte, capacity decay in repeated charge and discharge cycles was significantly reduced, compared with Comparative Example 1 in which TOX was not included.

[0186] Experimental Example 2. Battery performance evaluation as a function of TOX content and its results

[0187] For each battery of Example 1 to Example 4, performance evaluation was performed by the same method as in Experimental Example 1, and Figure 3 and Figure 4 The results are shown.

[0188] refer to Figure 3 and Figure 4 By adding TOX, the life characteristics of all batteries are improved. In particular, the life improvement performance is as follows: Example 4 (40 wt % added) < Example 3 (30 wt % added) < Example 1 (10 wt % added) < Example 2 (20 wt % added).

[0189] Experimental Example 3. Evaluation of battery performance as a function of electrolyte composition and its results

[0190] The performance of each battery of Example 2, Comparative Example 2 and Comparative Example 3 was evaluated by the same method as in Experimental Example 1, and Figure 5 and Figure 6 The results are shown.

[0191] refer to Figure 5 and Figure 6 , it was confirmed that the battery of Example 2 to which TOX was added showed much higher capacity retention performance in repeated charge and discharge cycles than Comparative Example 2 in which TOX was not added and a composition of 1,3-dioxolane and 1,2-dimethoxyethane (1 / 1 volume / volume) was used as the non-aqueous solvent. In particular, in the case of Comparative Example 3, since TOX was added, but as the composition of the non-aqueous solvent, a composition of 1,3-dioxolane and a carbonate-based solvent was included instead of a combination of the cyclic ether and the linear ether, it was found that the battery performance was very low. It is speculated that the battery performance degradation is caused by the side reaction between the carbonate-based solvent and the polysulfide.

[0192] Experimental Example 4. Evaluation of battery performance as a function of electrolyte composition and its results

[0193] For each battery of Example 5, Example 6, and Example 7, 0.1 C discharge and 0.1 C charge were repeated twice in the CC mode at 25° C. in the range between 1.8 V and 2.5 V, and then 0.1 C discharge was performed to activate the battery. Subsequently, 0.2 C charge and 0.3 C discharge cycles were repeated in the CC mode at 25° C. in the range between 1.8 V and 2.5 V to evaluate battery performance. In this case, charging and discharging were performed under a pressure of 7 atm applied to the battery using a pressurizing jig. Figure 7 , Figure 8 and Fig. 9 The evaluation results are shown.

[0194] refer to Figure 7 , Figure 8 and Fig. 9 No significant changes were found in the discharge protocols of Examples 5, 6, and 7 in which TOX was added to the electrolyte, but Example 5 showed a much longer battery life compared to Example 6 in which LiTFSI was used instead of the lithium salt and Example 7 in which DOL was used instead of 2-MeF as the cyclic ether in the non-aqueous solvent.

[0195] Therefore, it was confirmed that, when TOX was used in the electrolyte, it produced a high synergistic effect together with LiFSI as the lithium salt and a mixed solvent of 2-MeF and DME as the nonaqueous solvent.

Claims

1. An electrolyte for a lithium-sulfur battery, comprising: Non-aqueous solvents, lithium salts, nitrates / esters and tris alkyl, wherein the non-aqueous solvent comprises an ether solvent, and The ether solvent comprises cyclic ether and non-cyclic ether. 2 . The lithium-sulfur battery electrolyte according to claim 1 , wherein the content of the cyclic ether is 30% by volume or less based on the total volume of the nonaqueous solvent. 3 . The lithium-sulfur battery electrolyte according to claim 1 , wherein the content of the cyclic ether is 20% by volume or less based on the total volume of the nonaqueous solvent.

4. The lithium-sulfur battery electrolyte according to claim 1, wherein the content of the cyclic ether is 20% by volume or less based on the total volume of the nonaqueous solvent, and Wherein, based on the total volume of the non-aqueous solvent, the content of the non-cyclic ether is greater than 80 volume %. 5 . The lithium-sulfur battery electrolyte according to claim 1 , wherein the nonaqueous solvent does not contain a carbonate-based solvent.

6. The electrolyte for a lithium-sulfur battery according to claim 1, wherein the cyclic ether comprises 2-methylfuran, 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dihydropyran, 1,4-dihydropyran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetra ... alkane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, dimethyl isosorbide or a mixture thereof.

7. The electrolyte for a lithium-sulfur battery according to claim 1, wherein the acyclic ether comprises dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, butanediol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether, ethylene glycol ethyl methyl ether or a mixture thereof.

8. The lithium-sulfur battery electrolyte according to claim 1, wherein the three The content of alkane is 5 to 45 wt %.

9. The lithium-sulfur battery electrolyte according to claim 1, wherein the three The content of alkane is 10 to 20 wt %.

10. The lithium-sulfur battery electrolyte according to claim 1, wherein the three The weight ratio of alkane to the nitrate / ester is from 2 to 15.

11. A lithium-sulfur battery comprising: a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, wherein the electrolyte is as defined in any one of claims 1 to 10, and The positive electrode contains a sulfur-containing compound as a positive electrode active material.

12. The lithium-sulfur battery according to claim 11, wherein the sulfur-containing compound comprises inorganic sulfur (S8), Li2S n (n≥1), disulfide compounds, organic sulfur compounds, carbon-sulfur polymers (C2S x ) n , x is an integer from 2.5 to 50, n≥2) or a mixture thereof. 13 . The lithium-sulfur battery according to claim 11 , wherein the negative electrode comprises lithium metal, lithium alloy or a mixture thereof as a negative electrode active material. 14 . The lithium-sulfur battery according to claim 11 , wherein the lithium-sulfur battery is a coin type battery or a pouch type battery.